If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-25x + 55) = 0 Reorder the terms: (55 + -25x) = 0 Remove parenthesis around (55 + -25x) 55 + -25x = 0 Solving 55 + -25x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-55' to each side of the equation. 55 + -55 + -25x = 0 + -55 Combine like terms: 55 + -55 = 0 0 + -25x = 0 + -55 -25x = 0 + -55 Combine like terms: 0 + -55 = -55 -25x = -55 Divide each side by '-25'. x = 2.2 Simplifying x = 2.2
| 24+8x=8(3+8x) | | 8(m+3)-20+m= | | (z-6)11= | | a^2+8a+29=13 | | -24-3v=-6(2v+7) | | 8v+8v=2(-1+v)+9(v+8) | | 4(x+3)-14=7(x-2) | | -36=3f | | 3x+4y-18=0 | | 13v-7=6 | | 10=0.2a+2 | | 8p+24=-6(7-5p) | | 16x^2=25x | | X^2+8x+52=0 | | 2k+3=8 | | 4+t=-3 | | -8(-11a-1)=-6(-9a+10) | | 5x-18=2x-9 | | 2x^2=76x | | 4g=36 | | -8(1+v)+6v= | | -25-8x=7(5-4x) | | x^2+4=-12 | | 2b(b-7)(b+8)= | | -6m+5m+8m+1=-20 | | 7x+10=3x+46 | | 7x+2=2x+17 | | (5x-9)(x^2-3x-1)= | | 2x-8=12-2x | | -6x+4x-2x=0 | | 18y-20y=2y | | 13=4m-9-5m |